Kompetensi Guru dalam Memanfaatkan Sistem Informasi Manajemen Perpustakaan dalam Memaksimalkan Literasi Siswa - Azainil Azainil; Sudarman Sudarman; Evy Hanifah; Lailan Sawiyah Siagian; Nurdiansari Nurdiansari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Teachers are not only required to provide teaching. But more than that, they must provide literacy to students so that students have high abilities to find literacy that can support their learning development. This study emphasizes teacher competence in maximizing the library information system so that students are more active in finding learning references. The research method used to answer this problem is descriptive qualitative where researchers conducted interviews with teachers, library staff and students. The results of this study indicate the ineffectiveness of the library information system so that students are not interested in visiting the library website. In addition, students prefer to search for literacy through Google rather than using the library website. Finally, the library is unable to provide maximum contribution in providing literacy and information to students